Conflicts in religious life in Csongrád in the early 19th century reactions and attempted solutions - Gyöngyössy Orsolya (Religion, culture, society, 2015)
The article examines the conflict-fraught tenure of János Mátyus as parish priest of Csongrád (1802-1827), and evaluates the consequences and the re-actions of the parishioners. Above all, it seeks an answer to the question of the qualities on which a person was judged to be a “good priest”, who and what were regarded as incompatible with the ideal priest. How did the faithful express their disapproval of the priest who violated norms and how did the atypical behaviour of the Csongrád parish priest create what could be regarded as a collective “spir-itual crisis situation”?